FORMING ADAPTIVE SKILLS OF PRESCHOOL CHILDREN (Academicia Globe: Inderscience Research, 2024)
The article deals with the formation of adaptive skills of preschoolers. The content of the concept of “adaptation” is revealed. The development of abilities in preschool children is justified.